University Lecturers at Risk: A Systematic Review and Meta-Analysis of Cardiovascular Reactivity and Cardiometabolic Health Outcomes in the Nigerian Context - Jamilu Lawal Ajiya; Sarki Adamu Musa (CV Media Inti Teknologi, 2026)
Background: Stress linked to teaching has become a major issue for the health of university teachers, especially in developing nations like Nigeria. Heavy workloads, a lack of resources, and high academic expectations lead to increased physical stress reactions, which can harm heart health and contribute to diseases related to the heart and metabolism. Methods: This study used a meta-analysis and systematic review technique. Relevant studies from 2014 to 2024 were found using databases including Google Scholar, PubMed, Scopus, Web of Science, and AJOL. Twenty of the 82 studies that were first found, with a total of 2,430 participants, met the inclusion criteria. The data collected looked at heart rate, blood pressure, and research details. The Cochrane Risk of Bias Tool and the Newcastle-Ottawa Scale were used to assess the quality of the studies. Fixed-effect and random-effects models were used in a meta-analysis. Result: The results showed a clear link between stress from teaching and heart health issues. The average difference in blood pressure was between 5.23 and 5.51 mmHg, while the heart rate rose between 3.15 and 3.41 beats per minute. These findings point to heightened heart responses among university lecturers in Nigeria who face work-related stress, indicating a greater chance of developing heart diseases and metabolic disorders. Conclusion: Stress related to teaching has a major impact on heart health for university lecturers in Nigeria. The results emphasize the importance of specific programs to tackle stress, strategies for managing it, and changes to institutional policies to lower job-related stress and enhance heart health outcomes.